The phenomenon of Cashless as a Consumptive Lifestyle of Upper Middle-Class Net Generation Women in Surabaya - Tedjomurti, Febriandita (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2025)
Advances in information technology today make financial transactions easier, faster, and varied. The use of electronic-based payments will create a phenomenon called a cashless society. The formation of a cashless society that is full of conveniences and advantages can lead to consumptive behavior in society, especially in the net generation in the upper middle class because of the availability of facilities and infrastructure in urban areas such as the city of Surabaya. The focus of this research is twofold, namely how the consumptive behavior of the upper middle class net generation women who make cashless transactions in the city of Surabaya. and how can cashless transaction behavior change the consumptive lifestyle of women, especially the upper middle class net generation in the city of Surabaya. The method used in this study is a qualitative research using the theory of consumption society from Jean Baudrilard who sees the consumption process in modern society not only looking for use value but also on the value of the symbols in the goods or services. This study conducted in- depth interviews using the snowball technique to 14 informants, 9 people as subject informants, and 5 people as non-subject informants. Interviews were conducted using interview guidelines and resulted in the finding that several factors that became the background of changes in the types of payment transactions were the desire to always look up to date, the convenience and practicality of cashless payments, and the many benefits obtained during non-cash payments. Meanwhile, there are two categories of cashless behavior in the upper-middle class Net Generation women in Surabaya, namely the upper- middle class net generation who transact in full cashless and the second category is the upper- middle-class net generation who transact cashless according to profit. With the convenience and practicality, the Net Generation women in the middle-upper class Surabaya City easily behave more consumptively than using cash payments. They consider that cashless payments are a symbol of a modern lifestyle. Keywords: Cashless, Consumerism, Net Generation, Middle and High Class Society